An ironic approach to the Absolute Schlegel's poetic mysticism - Mirzakhan, Karolin (Lexington Books, 2020)
An Ironic Approach to the Absolute: Schlegel's Poetic Mysticism brings Friedrich Schlegel's ironic fragments in dialogue with the Dao De Jing and John Ashbery's Flow Chart to argue that poetic texts offer an intuition of the whole because they resist the reader's desire to comprehend them fully.